Effect of metformin on the anti-Müllerian hormone level in infertile women with polycystic ovarian syndrome - Fatemeh Foroozanfard; Mansooreh Samimi; Kosar Hosseini Almadani; Mojtaba Sehat (Electronic Physician, 2017)
Background: Polycystic ovary syndrome (PCOS) is the major cause of anovulatory infertility in women. The level of serum Anti-Mullerian Hormone (AMH) in patients can be 2-3 times higher than in healthy women. The aim of this study was to assess the effect of metformin on AMH level in PCOS patients suffering from infertility. Methods: In this pre and post clinical trial, 30 infertile patients with PCOS were enrolled according to the Rotterdam criteria. The serum AMH level was recorded before and after 8 weeks of treatment with metformin (1500 mg daily). We used SPSS version 17 and paired samples t-test, multiple linear regression and ANCOVA test for data analysis. Results: Serum AMH level was significantly decreased after 8 weeks of treatment with metformin [10±3.75 (ng/ml) versus 7.8±3.7 (ng/ml)] (p=0.008, 95% CI: 0.60-3.75). Also, AMH level change was directly associated to BMI in PCOS patients. In other words, in these patients, a higher BMI led to more decrease in AMH level after metformin treatment. Conclusion: Eight weeks’ treatment with metformin would significantly decrease AMH. AMH level change was directly associated to BMI. Clinical trial registration: The trial was registered at the Iranian Registry of Clinical Trials (http://www.irct.ir) with the Irct ID: 201403132967N5 Funding: This study was funded by the Department of Gynecology and Obstetrics, School of Medicine, Kashan University of Medical Sciences (Grant Number: 9322).